Flexible photocatalytic fuel cell photoanode, preparation method and application thereof

CN122992239APending Publication Date: 2026-10-27ANHUI UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611441583.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]本发明旨在提供一种柔性ZnO@ZIF-8核壳阵列光阳极及其制备方法与应用,以解决现有技术中ZnO基光阳极光生载流子复合率高、光腐蚀严重,ZIF-8壳层与ZnO之间界面结合力弱、壳层不均匀、易脱落,以及现有制备方法难以在柔性导电基底上低温均匀生长ZIF-8壳层,进而制约柔性光催化燃料电池光电性能与弯折稳定性的技术问题

Benefits of technology

(1)原位自模板生长,界面结合牢固:以ZnO纳米棒自身为唯一锌源与结构模板,低温下原位生成ZIF-8壳层,无需外加锌盐,工艺简单、成本低廉;核壳间通过Zn-N化学键耦合,有效改善了传统外加锌盐法壳层不均、界面结合力弱、易脱落的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992239A_ABST
    Figure CN122992239A_ABST
Patent Text Reader

Abstract

The application discloses a flexible photocatalytic fuel cell photoanode and a preparation method and application thereof. The photoanode is a ZnO@ZIF-8 core-shell nanorod array in-situ grown on an ITO-PET flexible conductive substrate, and the ZIF-8 shell layer is in-situ generated by a self-template method with the ZnO nanorod as a template and a unique zinc source. In the preparation, the ZnO nanorod array is first electrodeposited and grown in a low-temperature water bath, then the ZnO surface is partially dissolved to release Zn 2+ , and the ZIF-8 shell layer is generated by coordination with 2-methyl imidazole. The flexible photocatalytic fuel cell based on the photoanode has an electric energy output performance, can remove methylene blue, tetracycline and hexavalent chromium respectively, and is suitable for wearable self-powered and portable water body repair fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of photocatalytic materials, flexible electronic devices and environmental remediation technology, specifically relating to a flexible photocatalytic fuel cell photoanode and its preparation method and application. Background Technology

[0002] The photoanode is the core functional component of photocatalytic fuel cells, enabling photoelectric conversion, pollutant degradation, and power output. Its carrier separation efficiency, interfacial structure stability, and substrate compatibility directly determine the device's performance limits and application scenarios. With the development of portable environmental remediation and wearable electronics, new requirements have been placed on photoanodes, including flexibility, low-temperature fabrication, high photoelectric activity, and strong mechanical stability. ZnO nanorods, due to their high electron mobility, easily tunable morphology, and low fabrication cost, are a key research material in the field of photocatalysis. The metal-organic framework material ZIF-8, with its high specific surface area, matched band positions, and porous adsorption characteristics, can be used to passivate ZnO surface defects and promote photogenerated carrier separation, making it an ideal modification component for ZnO-based photoanodes.

[0003] Several patents have disclosed the preparation technology of ZnO and ZIF-8 composite structures. For example, Chinese patent CN107991350A discloses a method for preparing rod-shaped ZnO@ZIF-8. Using an alumina flat electrode as a substrate, a ZnO seed layer is prepared by spin coating, and ZnO nanorods are grown hydrothermally. Then, ZIF-8 is grown in situ at room temperature in a mixed solution of 2-methylimidazole and zinc acetate. The resulting material is used for low-temperature hydrogen gas sensing. Although this method achieves the preparation of ZnO@ZIF-8 composite structures, its application scenario is gas sensors. It does not perform band matching and carrier transport regulation for photoelectrocatalytic reactions, and does not have the photoelectric conversion and water pollutant catalytic degradation functions required by photoanodes. Its ZIF-8 growth process requires the addition of zinc acetate as a zinc source, rather than self-template growth with ZnO itself as a template and zinc source. The core-shell interface bonding is limited, and the shell is prone to peeling off. Moreover, the substrate is a rigid alumina flat electrode, which cannot be bent and cannot meet the application requirements of flexible wearable devices.

[0004] In the field of flexible ZnO-based functional materials, Chinese patent CN120600844A discloses a method for preparing a metal catalyst by growing a ZnO-derived ZIF structure on a flexible carbon nanotube film. Using carbon nanotube films, carbon cloth, etc., as an integrated substrate, a ZnO array is grown, and a ZIF structure is generated in situ and loaded with metal. The catalyst is then obtained through high-temperature pyrolysis for a zinc-air battery oxygen reduction catalyst. While this method achieves the preparation of a ZnO-derived ZIF structure on a flexible substrate, its application is limited to the electrocatalytic cathode of a zinc-air battery, designed for the oxygen reduction reaction, and does not involve the excitation, separation, and photoelectric conversion of photogenerated carriers. Furthermore, the preparation involves a high-temperature inert atmosphere pyrolysis process, which is incompatible with the upper temperature limit of ITO-PET flexible transparent conductive substrates, making it unsuitable for direct use in preparing transparent photoanodes. Chinese patent CN120869398A discloses a UV-biodegradable flexible tactile sensor containing ZnO components. It uses a cPPA / ZnO nanorod composite film as the functional layer, combined with an ITO-PET flexible electrode, to achieve pressure sensing using the piezoelectric effect of ZnO. Although this scheme uses an ITO-PET flexible substrate and ZnO material, it utilizes the piezoelectric properties of ZnO rather than its photoelectrocatalytic performance. Furthermore, ZnO is dispersed in the polymer matrix as a disordered filler and does not form an ordered nanorod array structure. Therefore, it does not have the ability to perform photoelectroelectric conversion and catalytic degradation of pollutants, and cannot be used as a photoanode in a photocatalytic fuel cell system.

[0005] At the level of photocatalytic fuel cell devices, Chinese patent CN117712401A discloses a portable photocatalytic fuel cell and its fabrication method. The method involves preparing a photoanode by ion beam deposition of TiO2 combined with hydrothermal and annealing processes, followed by encapsulation with a cathode and a hot-melt film to obtain a portable device. However, the photoanode in this solution is a TiO2 system and does not involve a ZnO@ZIF-8 core-shell structure. The fabrication process includes ion beam sputtering and high-temperature annealing, and it is not optimized for low-temperature fabrication on flexible transparent substrates, making it difficult to adapt to wearable flexible applications.

[0006] In summary, existing ZnO@ZIF-8 composite technologies are concentrated in gas sensing and electrocatalysis, without optimization for photoanodes in photocatalytic fuel cells, and rely on external zinc salts and rigid substrates. Flexible ZnO-based materials are mostly used in sensing and energy storage catalysis scenarios, without development of photoelectrocatalysis and water remediation functions. Existing photoanode systems and fabrication processes for portable photocatalytic fuel cells are difficult to adapt to the needs of flexible wearable devices. Currently, there is a lack of technical solutions that combine ZnO@ZIF-8 core-shell structures, flexible ITO-PET substrates, and low-temperature in-situ self-templating methods for photoanodes in photocatalytic fuel cells. Summary of the Invention

[0007] This invention aims to provide a flexible ZnO@ZIF-8 core-shell array photoanode, its preparation method, and its application, in order to solve the technical problems in the prior art, such as high recombination rate of photogenerated carriers, severe photocorrosion, weak interfacial bonding between ZnO and ZnO, uneven shell layer, easy detachment, and difficulty in uniformly growing ZIF-8 shell layer at low temperature on flexible conductive substrates by existing preparation methods, which restrict the photoelectric performance and bending stability of flexible photocatalytic fuel cells.

[0008] The objective of this invention can be achieved through the following technical solutions: A method for fabricating a flexible ZnO@ZIF-8 core-shell array photoanode includes the following steps: (1) Fabrication of ZnO nanorod arrays on ITO-PET flexible conductive substrate, specifically including: (a) Using flexible ITO-PET as the working electrode, a ZnO seed layer is formed on the surface of ITO-PET by constant potential electrodeposition under constant temperature conditions in a deposition solution containing Zn(NO3)2. (b) ITO-PET with a ZnO seed layer was placed in a reaction solution containing Zn(NO3)2·6H2O and ammonia water and reacted under water bath conditions to grow ZnO nanorod arrays on the ITO-PET substrate. (2) The product obtained in step (1) is placed in an organic solvent-water mixture containing 2-methylimidazole and subjected to a solvothermal reaction without the addition of zinc salt. ZnO nanorods themselves are used as the sole zinc source and structural template, and Zn is released through partial dissolution of the ZnO nanorod surface. 2+ By coordinating with 2-methylimidazole, a ZIF-8 shell is generated in situ on the surface of ZnO nanorods, resulting in a flexible ZnO@ZIF-8 core-shell nanorod array photoanode; the ZnO@ZIF-8 core-shell structure has Zn-N chemical bond interface coupling.

[0009] Preferably, the concentration of Zn(NO3)2 in the deposition solution in step (a) is 0.05–0.2 M, the deposition temperature is 60–80 °C, the deposition potential relative to the Ag / AgCl reference electrode is -2.0–-2.5 V, and the electrodeposition time is 60–120 s.

[0010] Preferably, in step (b), the concentration of Zn(NO3)2·6H2O in the reaction solution is 0.01–0.05 M, the volume fraction of ammonia is 0.5%–5%, the water bath reaction temperature is 70–90°C, and the water bath reaction time is 6–12 h.

[0011] More preferably, in step (a), the concentration of Zn(NO3)2 in the deposition solution is 0.1 M, the deposition temperature is 70 °C, the deposition potential relative to the Ag / AgCl reference electrode is -2.5 V, and the deposition time is 90 s; in step (b), the concentration of Zn(NO3)2·6H2O is 0.035 M, the volume fraction of ammonia is 5%, the water bath reaction temperature is 80 °C, and the water bath reaction time is 10 h.

[0012] Preferably, the solvothermal reaction temperature in step (2) is 60-80℃ and the time is 16-32 h; the organic solvent-water mixed solution is DMF / H2O with a volume ratio of (2-4):1, and the concentration of 2-methylimidazole is 3-10 g / L.

[0013] The present invention also provides a flexible photocatalytic fuel cell photoanode, which is prepared by the above method; the photoanode includes an ITO-PET flexible conductive substrate and a ZnO@ZIF-8 core-shell nanorod array vertically grown on the substrate surface. The ZnO@ZIF-8 core-shell nanorod array is composed of ZnO nanorods and a ZIF-8 shell layer covering its surface. The ZnO@ZIF-8 core-shell structure has Zn-N chemical bond interface coupling.

[0014] Preferably, the ZnO nanorods have a diameter of 100–200 nm and a length of 1–2 μm; the ZIF-8 shell thickness is 30–40 nm.

[0015] The present invention also provides a flexible photocatalytic fuel cell, comprising the above-mentioned flexible photocatalytic fuel cell photoanode, and further comprising a self-breathing cathode, a membrane, and an encapsulation layer; the photoanode, membrane, and self-breathing cathode are stacked in sequence, and the encapsulation layer is an EVA hot melt film, which also serves as the upper and lower light-transmitting encapsulation layer and the surrounding encapsulation layer.

[0016] Preferably, the self-breathing cathode is a waterproof and breathable membrane coated with a conductive catalytic layer; the diaphragm is a degreased cotton sheet; and the electrolyte of the flexible photocatalytic fuel cell is artificial sweat or water containing organic pollutants or heavy metal ions.

[0017] The present invention also provides the application of the above-mentioned flexible photocatalytic fuel cell photoanode in power output, water pollution remediation or wearable self-powered devices.

[0018] Preferably, the water pollution includes organic dyes, antibiotics, or hexavalent chromium ions.

[0019] Compared with the prior art, the present invention has the following outstanding advantages: (1) In-situ self-template growth with strong interface bonding: ZnO nanorods themselves are the only zinc source and structural template. ZIF-8 shells are generated in-situ at low temperature without the need for external zinc salts. The process is simple and low-cost. The core and shell are coupled by Zn-N chemical bonds, which effectively improves the problems of uneven shells, weak interface bonding and easy detachment in the traditional external zinc salt method.

[0020] (2) The carrier separation efficiency is significantly improved and photocorrosion is suppressed: The ZIF-8 shell has both surface passivation and heterojunction regulation functions, which can effectively suppress photogenerated electron-hole recombination; at the same time, the shell can block the electrolyte from direct contact with the ZnO core, significantly alleviate photocorrosion, and improve long-term operational stability.

[0021] (3) Low-temperature preparation adapts to flexible substrates and has excellent bending stability: The entire preparation temperature does not exceed 90℃, and it has good compatibility with ITO-PET flexible substrates. The resulting photoanode has good mechanical flexibility and is suitable for the repeated deformation requirements of wearable devices.

[0022] (4) Supporting flexible devices to achieve multifunctional integration: The flexible photocatalytic fuel cell built based on this photoanode can output electrical energy in artificial sweat or polluted water, and can degrade methylene blue, tetracycline and reduce hexavalent chromium ions respectively, and is suitable for wearable self-powered, outdoor emergency water purification and other scenarios.

[0023] (5) Easy to scale up and integrate devices: The preparation process is mild and does not require expensive vacuum equipment and high-temperature sintering process, and can be scaled up; the battery cells can be connected in series and parallel to form a flexible battery pack, which has the potential to power low-power sensors and small electronic components. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the fabrication process of the flexible ZnO@ZIF-8 core-shell array photoanode of the present invention; Figure 2 The images show SEM, TEM, and HRTEM images of the ZnO nanorod array and the ZnO@ZIF-8 core-shell nanorod array prepared in this invention; wherein, (a) is the SEM image of the ZnO nanorod array, (b) is the TEM image of the ZnO nanorods, (c) is the HRTEM image of the ZnO nanorods, (d) is the SEM image of the ZnO@ZIF-8 core-shell nanorod array, (e) is the TEM image of the ZnO@ZIF-8 core-shell nanorods, and (f) is the HRTEM image of the ZnO@ZIF-8 core-shell nanorods. Figure 3 The XRD pattern of the ZnO@ZIF-8 core-shell nanorod array prepared in this invention; Figure 4XPS spectra of the ZnO@ZIF-8 core-shell nanorod array prepared in this invention; where (a) is the full XPS spectrum, (b) is the N 1s fine spectrum, (c) is the Zn 2p fine spectrum, and (d) is the O 1s fine spectrum. Figure 5 The images show the Mott-Schottky curves, UV-Vis spectra, effects of the scavenger on photocatalytic performance, and band structure and photogenerated carrier migration mechanism of the ZnO@ZIF-8 heterojunction for ZnO and ZIF-8, respectively. (a) shows the Mott-Schottky curve of ZnO, (b) shows the Mott-Schottky curve of ZIF-8, (c) shows the UV-Vis spectra of ZnO and ZnO@ZIF-8, (d) shows the UV-Vis spectrum of ZIF-8, (e) shows the effects of the scavenger on photocatalytic performance, and (f) shows the band structure and photogenerated carrier migration mechanism of the ZnO@ZIF-8 heterojunction. Figure 6 The transient photocurrent response curves, electrochemical impedance spectra, and linear sweep voltammetry curves of ZnO and ZnO@ZIF-8 photoanodes prepared in this invention are shown; wherein, (a) is the transient photocurrent response curve, (b) is the electrochemical impedance spectrum, and (c) is the linear sweep voltammetry curve. Figure 7 The image shows a comparison of the photocatalytic degradation / reduction performance of ZnO and ZnO@ZIF-8 photoanodes prepared in this invention on methylene blue, tetracycline and Cr(VI); where (a) is the degradation curve of methylene blue, (b) is the degradation curve of tetracycline and (c) is the reduction curve of Cr(VI). Figure 8 This is a schematic diagram of the layered structure of the flexible photocatalytic fuel cell of the present invention, wherein the self-breathing cathode is composed of a conductive silver paste catalyst layer and a PTFE waterproof and breathable membrane, and the upper and lower light-transmitting films are both EVA hot-melt films, which also serve as encapsulation layers; Figure 9 The figures show the short-circuit current density curve, open-circuit voltage curve, polarization curve, and power density curve of the flexible photocatalytic fuel cell of the present invention in flat and bent states; wherein, (a) is the short-circuit current density curve, (b) is the open-circuit voltage curve, and (c) is the polarization curve and power density curve. Figure 10 These are physical images of the flexible photocatalytic fuel cell of the present invention in both flat and bent states. Detailed Implementation

[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] In this invention, the water bath reaction is also known as the water bath method.

[0027] This invention provides a flexible photocatalytic fuel cell photoanode, which is a ZnO@ZIF-8 core-shell nanorod array grown in situ on an ITO-PET substrate using a self-templating method.

[0028] Table 1: Fabrication parameters of flexible ZnO@ZIF-8 core-shell nanorod array photoanode Table 2: Specifications of Components in Flexible Photocatalytic Fuel Cells Note: “—” in the table indicates that the part has no specific size / shape / thickness limit, or that the item is not applicable.

[0029] The self-breathing cathode used in this embodiment of the invention is a PTFE waterproof and breathable membrane coated with a silver paste conductive catalytic layer, and its preparation method is as follows: Commercial silver paste was uniformly coated onto one side of the PTFE waterproof and breathable membrane (specifications see Table 2) using a screen printing method, covering the entire 1×1 cm area. 2 The coated PTFE membrane was placed in a 70°C drying oven for 2 hours to allow the silver paste to solidify and form a conductive layer, thus obtaining the self-breathing cathode.

[0030] The diaphragm used in this embodiment of the invention is a degreased cotton sheet, and its pretreatment method is as follows: Cut commercially available degreased cotton sheets to the required size (see Table 2 for specifications), ultrasonically clean them with anhydrous ethanol and deionized water for 10 min each, and dry them in a 50℃ drying oven for 2 h before use.

[0031] In this embodiment of the invention, a hot melt film is used for encapsulation, and the encapsulation conditions are as follows: The cut hot-melt film (EVA, specifications see Table 2) was placed on the upper and lower surfaces and four edges of the photoanode and cathode stack, and hot-pressed at 120℃ and 0.2 MPa pressure for 10 s, leaving one side as an electrolyte injection / release port. After injecting electrolyte through the injection / release port, the injection / release port was sealed under the same encapsulation conditions to obtain the flexible photocatalytic fuel cell unit (effective working area 1×1 cm). 2 ).

[0032] Example 1: Preparation of flexible ZnO@ZIF-8 core-shell nanorod photoanodes.

[0033] Preparation process as follows Figure 1 As shown, the specific steps include: (1) Preparation of ZnO nanorod arrays: A three-electrode electrochemical deposition system was used, with ITO-PET as the working electrode (deposition area 1×1 cm). 2 A platinum electrode was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. The deposition solution was a 0.10 mol / L Zn(NO3)2 aqueous solution. Deposition was carried out at a constant potential of -2.5 V relative to the Ag / AgCl reference electrode for 90 s under a constant temperature water bath at 70℃. After deposition, the sample was washed with deionized water and dried in air at 50℃ to obtain ITO-PET with a seed layer.

[0034] The ITO-PET substrate with the seed layer was placed in the reaction solution. The reaction solution was prepared by mixing 40 mL of deionized water, 0.416 g of Zn(NO3)2·6H2O, and 2 mL of NH3·H2O. The reaction solution was poured into a beaker, the mouth of the beaker was sealed with plastic wrap, and the beaker was placed in an 80℃ water bath and reacted at normal pressure for 10 h. After the reaction was completed, the sample was removed, thoroughly washed with ethanol and deionized water in sequence, and then naturally dried to obtain a ZnO nanorod array uniformly grown on the ITO-PET substrate. The diameter and length of the ZnO nanorods are shown in Table 1.

[0035] Figure 2 In the middle (a), there is a SEM image of the obtained ZnO nanorod array, showing that the ZnO nanorods grow uniformly on the substrate and have a smooth surface. Figure 2 In the middle (b) and (c), respectively, the TEM and HRTEM images of the ZnO nanorods show that the ZnO nanorods are solid structures with a lattice spacing of 0.248 nm, corresponding to the (101) crystal plane of the densely packed hexagonal ZnO.

[0036] (2) Preparation of ZnO@ZIF-8 core-shell nanorod array: like Figure 1As shown, ZnO@ZIF-8 was prepared using a self-templating method. 0.10 g of 2-methylimidazole was added to a 25 mL reactor containing 16 mL of a DMF / H2O mixed solvent (volume ratio 3:1), and the ITO-PET with ZnO nanorods grown in step (1) was placed inside. The reactor was then placed in a 70℃ oven for a solvothermal reaction for 24 hours. After the reaction, the reactor was washed multiple times with ethanol and naturally dried to obtain a ZnO@ZIF-8 core-shell nanorod array. The specifications of the ZnO nanorods and the ZIF-8 shell are shown in Table 1.

[0037] Figure 2 Image (d) shows the SEM image of the product after ZnO and ZIF-8 are combined. The SEM image clearly shows that the ZnO nanorods are uniformly coated with the adhering material. Figure 2 The TEM and HRTEM images in (e) and (f) further confirm the existence of the core-shell structure: the interior consists of ZnO nanorods, the outer shell has a uniform thickness (see Table 1), and a clear core-shell interface can be observed in the HRTEM.

[0038] Example 2: Material structure and mechanism characterization.

[0039] (1) X-ray diffraction (XRD) characterization XRD tests were performed on ITO-PET substrates, pure ZnO nanorods, and ZnO@ZIF-8 core-shell nanorod composites. The results are as follows: Figure 3 As shown. The characteristic diffraction peaks at 25.53° and 53.55° are the background signals of the ITO-PET substrate. In the XRD pattern of pure ZnO nanorods, the characteristic diffraction peaks at 34.35°, 36.14°, 47.38°, and 62.72° correspond to the (002), (101), (102), and (110) crystal planes of hexagonal ZnO, respectively. The diffraction peaks are sharp and there are no obvious impurity peaks, indicating that the prepared ZnO has good crystallinity and high purity. Compared with the XRD pattern of ZnO, the XRD pattern of ZnO@ZIF-8 composite material shows new characteristic diffraction peaks at 7.23°, 12.64° and 17.95°, which correspond to the (011), (112) and (222) crystal planes of ZIF-8, respectively. The peak positions of other diffraction peaks are basically the same as those of ZnO sample. No new impurity peaks appear, indicating that no new crystal phases appear in the pattern, and the core-shell heterostructure of ZnO@ZIF-8 was successfully constructed.

[0040] (2) X-ray photoelectron spectroscopy (XPS) characterization XPS analysis was performed on pure ZnO and ZnO@ZIF-8 composite materials, and the results are as follows: Figure 4 As shown. Figure 4(a) shows that ZnO@ZIF-8 is composed of N, C, O and Zn elements. Figure 4 In the middle (b), the N 1s fine spectrum shows that the two peaks with binding energies of 398.9 eV and 400.2 eV are attributed to the N atoms in the Zn-N bond and the O-Zn-N bond, respectively, indicating the presence of Zn-N bonding in the composite material. Figure 4 Image (c) shows the fine 2p spectrum of Zn. The binding energies of Zn 2p³ / 2 and Zn 2p¹ / 2 in the pure ZnO sample are located at 1021.7 eV and 1044.6 eV, respectively. The corresponding binding energies of the ZnO@ZIF-8 sample shift to 1021.2 eV and 1044.1 eV, a decrease of 0.5 eV compared to ZnO, indicating that electrons are transferred from ZIF-8 to ZnO. At the same time, the intensity of the Zn characteristic peak is significantly weakened, which is due to the shielding effect of the ZIF-8 shell on the internal ZnO signal. Figure 4 The middle (d) is the O 1s fine spectrum. In the pure ZnO sample, the binding energy of lattice oxygen is 530.4 eV and the binding energy of adsorbed oxygen is 532.0 eV. In the ZnO@ZIF-8 sample, the lattice oxygen (OC) peak is located at 530.4 eV and the adsorbed oxygen (OL) peak is located at 531.8 eV. The relative peak intensity of the OL peak increases, which is attributed to the ZnO surface being covered by ZIF-8.

[0041] The formation of the ZnO@ZIF-8 core-shell structure was confirmed by SEM, TEM, XRD, XPS, etc., in which ZnO and ZIF-8 are bonded through the interface Zn-N, and there is electron transfer from ZIF-8 to ZnO.

[0042] (3) Characterization of band structure and heterojunction mechanism For comparative characterization, a separate ZIF-8 sample was prepared. This separate ZIF-8 sample was used only for comparative testing and does not represent the preparation method of ZnO@ZIF-8 in this invention; in this invention, the ZIF-8 shell uses ZnO nanorods themselves as the sole zinc source, without the addition of zinc salts. The separate ZIF-8 sample was prepared using a solvothermal method: under conditions without ZnO nanorods, 2-methylimidazole and zinc acetate were reacted in a DMF / H2O mixed solution at 70°C for 24 h to obtain pure ZIF-8 powder. The MS test electrode was prepared by coating the sample onto the surface of an ITO-PET electrode using a drop-coating method.

[0043] To elucidate the band alignment and photogenerated carrier migration mechanism between ZnO and ZIF-8, Mott-Schottky (MS) and UV-Vis spectroscopy were performed on both. MS measurements were conducted in 0.5 M Na₂SO₄ solution at frequencies of 1000 Hz, 2000 Hz, 3000 Hz, and 5000 Hz. The vertical axis C in the figure is shown below. -2The unit is 10 12 F -2 MS test results are as follows: Figure 5 As shown in (a) and (b), the MS curves of ZnO and ZIF-8 both exhibit positive slopes, indicating that both are typical n-type semiconductors. Linear fitting calculations show that their flat-band potentials are 0.20 V and -2.30 V (vs. Ag / AgCl), respectively, which translate to 0.40 V and -2.10 V respectively after conversion to standard hydrogen electrode potentials (vs. NHE). For n-type semiconductors, the flat-band potential is very close to the conduction band (CB) edge potential; therefore, the above flat-band potentials can be approximated as the conduction band potentials of both.

[0044] Figure 5 In the middle (c), the UV-Vis absorption spectra of ZnO and ZnO@ZIF-8 are shown. Both have obvious absorption edges in the ultraviolet region. Figure 5 In the middle (d), the UV-Vis absorption spectrum of the independent ZIF-8 sample is shown, with its absorption edge located in a shorter wavelength region. Combining the optical bandgap widths obtained from UV-Vis spectroscopy (ZnO: 2.87 eV, ZIF-8: 5.16 eV), the valence band (VB) potentials of ZnO and ZIF-8 are further calculated using the formula E(VB) = E(CB) + Eg, resulting in 3.27 V and 3.06 V (vs. NHE), respectively.

[0045] Figure 5 The middle (e) represents the effect of different trapping agents on the photocatalytic performance of ZnO@ZIF-8, with the ordinate representing relative activity; where AO (ammonium oxalate), IPA (isopropanol), BQ (benzoquinone), and K2Cr2O7 are represented as holes (h + ), hydroxyl radicals (·OH), superoxide radicals (·O2) - ) and electrons (e - ) capture agent.

[0046] Based on the above results, a band arrangement and photogenerated carrier migration model for the ZnO@ZIF-8 heterojunction was constructed. Figure 5 (f) : After ZnO and ZIF-8 come into close contact, a type II heterojunction structure may be formed. Under simulated sunlight irradiation, both may be excited by photons to generate photogenerated electron-hole pairs. Driven by the energy level difference, photogenerated electrons may migrate from ZIF-8, which has a higher conduction band potential, to the conduction band of ZnO, while holes may migrate along the valence band gradient from ZnO to the valence band of ZIF-8. This process may achieve effective separation of photogenerated electron-hole pairs and suppress carrier recombination, which may be one of the reasons for the improved photoelectric properties and photocatalytic activity of the composite material of this invention.

[0047] Example 3: Characterization of the photoelectrochemical and photocatalytic properties of the materials.

[0048] (1) Photoelectrochemical (PEC) performance The test employed a three-electrode system, using ZnO or ZnO@ZIF-8 photoanode as the working electrode, a Pt sheet as the counter electrode, and Ag / AgCl as the reference electrode. The electrolyte was a 0.5 M Na₂SO₄ solution. The light source was a xenon lamp (AM 1.5G, 100 mW / cm²). 2 The transient photocurrent test bias voltage was 0.5 V (vs. Ag / AgCl), the EIS test frequency range was 0.1 Hz to 100 kHz, the perturbation amplitude was 10 mV, and the LSV scan rate was 10 mV / s. The working area was 1 × 1 cm⁻¹. 2 .

[0049] Figure 6 Figure (a) shows the transient photocurrent density response curves of the ZnO and ZnO@ZIF-8 photoanodes prepared in Example 1. It can be seen that the photocurrent density of all photoanodes rapidly reaches its maximum value under illumination and immediately recovers to its initial state after the light source is turned off, indicating that these photoanodes have excellent photoresponse capabilities. The photocurrent density of the ZnO photoanode is approximately 12 μA / cm². 2 The photocurrent density of ZnO@ZIF-8 is significantly higher than that of ZnO, reaching 22 μA / cm. 2 . Figure 6 Figure (b) shows the electrochemical impedance spectroscopy (EIS) spectra of ZnO and ZnO@ZIF-8 samples under simulated sunlight. In the EIS, the smaller the radius of the Nyquist semicircle, the higher the charge transfer rate. Figure 6 As shown in Figure (b), the Nyquist plot radius of ZnO@ZIF-8 is significantly smaller than that of ZnO, indicating that the charge transfer rate of the sample is improved after growing ZIF-8. Figure 6 (c) shows the linear sweep voltammetry curves of all samples, which can be seen that the photocurrent response was significantly improved after the growth of ZIF-8.

[0050] (2) Photocatalytic degradation / reduction performance The initial concentrations of methylene blue (MB) were 10 mg / L, tetracycline (TC) 20 mg / L, and Cr(VI) 10 mg / L. All solutions were 50 mL in volume and neutral in pH. The light source was a xenon lamp (AM 1.5G, 100 mW / cm²). 2 The working area of ​​the photoanode is 1×1 cm. 2 Concentrations were measured using a UV-Vis spectrophotometer.

[0051] Figure 7In Figure (a), the degradation curves of methylene blue (MB) solution by the ZnO and ZnO@ZIF-8 photoanodes prepared in Example 1 are shown. The pure ZnO sample exhibited certain photocatalytic activity, with a C / C ratio of approximately 0.50 after 6 hours (degradation rate of approximately 50%). The degradation performance of the ZnO@ZIF-8 composite material was significantly enhanced, with the C / C ratio decreasing to approximately 0.33 after 6 hours, achieving a degradation rate of 67%. Figure 7 Figure (b) shows a comparison of the degradation efficiency of tetracycline (TC) solution. Within 2 hours, the degradation rate of ZnO@ZIF-8 reached 70%, while the degradation rate of pure ZnO was only 25%, indicating that the composite of ZIF-8 significantly improved the ability to degrade tetracycline. Figure 7 Figure (c) shows a comparison of the reduction efficiency of Cr(VI) solution. Within 6 hours, the reduction efficiency of ZnO@ZIF-8 was significantly better than that of pure ZnO, reaching 87.7%, which is 1.84 times that of pure ZnO (47.8%). This indicates that the ZIF-8 composite significantly improves the ability to reduce Cr(VI).

[0052] Example 4: Assembly and photoelectrochemical performance of flexible photocatalytic fuel cells.

[0053] ZnO nanorods and ZnO@ZIF-8 core-shell nanorod composites grown on ITO-PET substrates prepared in Example 1 were used as photoanodes to assemble flexible photocatalytic fuel cells (fPFCs). A schematic diagram of the layered structure of the device is shown below. Figure 8 As shown. The specific assembly method is as follows: Use the components listed in Table 2 (photoanode 1.5 × 1.5 cm). 2 / Working area 1×1 cm 2 1.2 × 1.2 cm absorbent cotton diaphragm 2 1×1 cm PTFE cathode coated with silver paste 2 EVA hot melt film 1.8 × 1.8 cm 2 The photoanode, separator, and cathode are stacked sequentially. An EVA hot-melt film is then hot-pressed onto the top and bottom surfaces and edges of the photoanode-cathode stack (120℃, 0.2 MPa, 10 s), simultaneously forming upper and lower transparent encapsulation layers and a perimeter encapsulation layer. One side is left as an electrolyte injection / release port. Simulated artificial sweat is injected through the injection / release port as the electrolyte. The injection / release port is then sealed using the same encapsulation conditions, resulting in a flexible photocatalytic fuel cell unit (effective working area 1×1 cm²). 2 ).

[0054] Using simulated artificial sweat (0.0100 mol / L urea, 0.0428 mol / L sodium chloride, 2.78 × 10⁻⁶ ... -4The electrolyte solution consisted of 0.0195 mol / L glucose and 0.0195 mol / L lactic acid. The simulated light source was a xenon lamp (AM 1.5G, 100 mW / cm²). 2 The bending condition involved bending the device around a cylinder with a radius of curvature of approximately 1 cm. Tests were conducted at room temperature under simulated sunlight (xenon lamp, AM1.5G, 100 mW / cm²). 2 The photoelectrochemical performance was tested under the following conditions, and the results are as follows: Figure 9 As shown.

[0055] Figure 9 In the middle (a), the short-circuit current density curve of a single fPFC under simulated illumination is shown. Figure 9 (b) shows the open-circuit voltage curve of a single fPFC under simulated illumination. The photocurrent density of the ZnO fPFC in its flat state is approximately 18 μA / cm². 2 The photocurrent density in the bent state is approximately 22 μA / cm. 2 The photocurrent density of ZnO@ZIF-8 fPFC is significantly higher than that of ZnO, reaching approximately 42 μA / cm² in a flat state. 2 The photocurrent density in the bent state is approximately 40 μA / cm. 2 . Figure 9 Figure (c) shows the polarization and power density curves of the fPFC. Compared to the ZnO fPFC, the ZnO@ZIF-8 fPFC exhibits less polarization, resulting in a higher actual output voltage at the same current density and reduced internal energy loss. The maximum power density of the ZnO fPFC in its flat state is 6.9 μW / cm². 2 The value is 6.3 μW / cm under bending conditions. 2 The ZnO@ZIF-8 fPFC achieves a maximum power density of 18.3 μW / cm² in its flat configuration. 2 It reaches 16.2 μW / cm under bending conditions. 2 Although the performance of fPFC decreases slightly in the bent state due to the reduced light-receiving area, the fPFC of ZnO@ZIF-8 is still significantly higher than that of ZnO. Figure 10 The images show actual photos of the device in its flat and bent states, demonstrating its excellent flexibility.

[0056] The flexible ZnO@ZIF-8 core-shell nanorod photoanode provided by this invention has a simple and mild fabrication process with inexpensive and readily available raw materials. It can be grown in situ on a flexible ITO-PET substrate and exhibits photoelectrochemical properties and photocatalytic degradation / reduction capabilities. The flexible photocatalytic fuel cell based on this photoanode has power generation capabilities and can maintain performance even when bent, making it suitable for wearable self-powered devices and portable water remediation applications.

[0057] It should be noted that the above embodiments are merely preferred embodiments of the present invention, used to explain the technical principles and application effects of the present invention, and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions, modifications, or improvements made based on the technical concept of the present invention within the spirit and principles of the present invention should be included within the scope of protection of the present invention. In practical applications, those skilled in the art can make adaptive adjustments to the relevant parameters according to the specific test materials, working conditions, and accuracy requirements, all of which fall within the scope of protection of the present invention.

Claims

1. A method for preparing a flexible photocatalytic fuel cell photoanode, characterized in that, Includes the following steps: (1) Fabrication of ZnO nanorod arrays on ITO-PET flexible conductive substrate, specifically including: (a) Using flexible ITO-PET as the working electrode, a ZnO seed layer was formed on the surface of ITO-PET by electrodeposition for 60-120 s in a deposition solution containing 0.05-0.2 M Zn(NO3)2 at 60-80 °C and at a potential of -2.0--2.5 V relative to the Ag / AgCl reference electrode. (b) ITO-PET with ZnO seed layer was placed in a reaction solution containing 0.01-0.05 M Zn(NO3)2·6H2O and 0.5-5% ammonia water by volume, and reacted in a water bath at 70-90℃ for 6-12 h to grow ZnO nanorod arrays on ITO-PET substrate. (2) The product obtained in step (1) is placed in an organic solvent-water mixture containing 2-methylimidazole and subjected to a solvothermal reaction without the addition of zinc salt. ZnO nanorods themselves are used as the sole zinc source and structural template, and Zn is released through partial dissolution of the ZnO nanorod surface. 2+ By coordinating with 2-methylimidazole, a ZIF-8 shell is generated in situ on the surface of ZnO nanorods, resulting in a flexible ZnO@ZIF-8 core-shell nanorod array photoanode; the ZnO@ZIF-8 core-shell structure has Zn-N chemical bond interface coupling.

2. The preparation method according to claim 1, characterized in that, In step (a), the concentration of Zn(NO3)2 in the deposition solution is 0.1 M, the deposition temperature is 70 °C, the deposition potential relative to the Ag / AgCl reference electrode is -2.5 V, and the deposition time is 90 s; in step (b), the concentration of Zn(NO3)2·6H2O is 0.035 M, the volume fraction of ammonia is 5%, the water bath reaction temperature is 80 °C, and the water bath reaction time is 10 h.

3. The preparation method according to claim 1, characterized in that, The solvothermal reaction temperature in step (2) is 60-80℃ and the time is 16-32 h; the organic solvent-water mixed solution is DMF / H2O with a volume ratio of (2-4):1, and the concentration of 2-methylimidazole is 3-10 g / L.

4. A flexible photocatalytic fuel cell photoanode, characterized in that, The photoanode is prepared by the method described in any one of claims 1 to 3; the photoanode comprises an ITO-PET flexible conductive substrate and a ZnO@ZIF-8 core-shell nanorod array grown vertically on the substrate surface, the ZnO@ZIF-8 core-shell nanorod array being composed of ZnO nanorods and a ZIF-8 shell layer covering its surface, the ZnO@ZIF-8 core-shell structure having Zn-N chemical bond interface coupling.

5. The photoanode according to claim 4, characterized in that, The ZnO nanorods have a diameter of 100–200 nm and a length of 1–2 μm; the ZIF-8 shell has a thickness of 30–40 nm.

6. A flexible photocatalytic fuel cell, comprising the flexible photocatalytic fuel cell photoanode according to any one of claims 4 to 5, characterized in that, It also includes a self-breathing cathode, a diaphragm, and an encapsulation layer; the photoanode, diaphragm, and self-breathing cathode are stacked in sequence, and the encapsulation layer is an EVA hot melt film, which also serves as the top and bottom light-transmitting encapsulation layer and the surrounding encapsulation layer.

7. The flexible photocatalytic fuel cell according to claim 6, characterized in that, The self-breathing cathode is a waterproof and breathable membrane coated with a conductive catalytic layer; the diaphragm is a degreased cotton sheet; and the electrolyte of the flexible photocatalytic fuel cell is artificial sweat or water containing organic pollutants or heavy metal ions.

8. The application of the flexible photocatalytic fuel cell photoanode as described in any one of claims 4 to 5, characterized in that, The flexible photocatalytic fuel cell photoanode can be applied to power output, water pollution remediation, or wearable self-powered devices.

9. The application according to claim 8, characterized in that, The water pollution includes organic dyes, antibiotics, or hexavalent chromium ions.

Citation Information

Patent Citations

  • Preparation of rod-like ZnO / ZIF-8 and low temperature H2 sensitive effect of rod-like ZnO / ZIF-8

    CN107991350A

  • Portable photocatalytic fuel cell as well as preparation method and application thereof

    CN117712401A

  • Preparation method for ZnO-derived zeolite imidazole ZIF structure supported metal catalyst grown on flexible carbon nanotube film

    CN120600844A

  • Tactile sensor of ultraviolet light degradable composite film and preparation method of tactile sensor

    CN120869398A